2006
DOI: 10.1007/s10526-006-9030-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of Microplitis bicoloratus on Spodoptera litura and implications for biological control

Abstract: Abstract. Microplitis bicoloratus Chen (Hymenoptera:Braconidae:Microgastrinae), a new species of Microplitis Fo¨rster from China, is a solitary endoparasitoid of the larvae of the cotton leafworm, Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae). This parasitoid is the first to be successfully reared and evaluated in the laboratory as a potential agent for the biological control of S. litura in China. Oviposition, immature development, and the effects of parasitism on the development of S. litura were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…I). In our samples, C. flavipes larvae eclosed between days three and four after parasitization, as observed for several other endoparasitoids (EGUILEOR et al 2001, LUO et al 2007, YU et al 2008. Daily larval mandible measurements showed that the first molt occurred between the 5 th and 6 th day after oviposition, while the second molt was observed between the 7 th and 8 th day (Tab.…”
Section: Resultssupporting
confidence: 83%
“…I). In our samples, C. flavipes larvae eclosed between days three and four after parasitization, as observed for several other endoparasitoids (EGUILEOR et al 2001, LUO et al 2007, YU et al 2008. Daily larval mandible measurements showed that the first molt occurred between the 5 th and 6 th day after oviposition, while the second molt was observed between the 7 th and 8 th day (Tab.…”
Section: Resultssupporting
confidence: 83%
“…The other prominent change after M. bicoloratus parasitism is developmental retardation of S. litura (Luo et al., ). We tested any involvement of F o F 1 ‐ATPase β‐chain in the development of S. litura .…”
Section: Resultsmentioning
confidence: 99%
“…The other prominent change after M. bicoloratus parasitism is developmental retardation of S. litura (Luo et al, 2007).…”
Section: Partial Loss Of F O F 1 -Atpase -Chain Inhibits the Developmmentioning
confidence: 99%
“…Adults were also provided with honey as a dietary supplement. Passage of parasitoids was performed according to established methods (Luo et al., ).…”
Section: Methodsmentioning
confidence: 99%